Поврзаност на полиморфизмите на гените вклучени во метаболизмот на циклофосфамид и доксорубицин со токсичните ефекти при нивната примена кај карциномот на дојката - Исмаили, Илир (Медицински факултет, УКИМ, Скопје, 2021)
Breast cancer is a major morbidity and mortality factor and is among the most frequent female neoplasms globally. Combined cyclophosphamide and doxorubicin adjuvant chemotherapy is frequently associated with a series of toxic effects of different grades and clinical significance. Constitutive polymorphisms in the genes involved in detoxification and metabolism of chemotherapeutics plays a key role in toxic effects predisposition. The main goal of this study is to determine the genetic association of polymorphisms rs20325282 in ABCB1 gene and rs1695 (A313G) in GSTP1 gene with occurrence of leukopenia and to estimate the possible predictive value of those polymorphisms regarding the risk of toxic effects and adverse reactions. The polymorphisms were genotyped in DNA samples from 178 cases of breast cancer treated adjuvantly with cyclophosphamide and doxorubicin, after providing the signed consent from each patient. Statistical analyses were performed comparing the clinical data regarding the toxic effects and adverse reactions with the freqeuncies of the genotypes and alleles of both polymorphisms. The analyses indicated that polymorphisms rs20325282 in ABCB1 gene and rs1695 in GSTP1 may have a predictive value in determing the probability and/or risk of occurence of chemotherapy-induced anemia, fever, febrile neutropenia and oral mucositis. Those findings could be used prospectively for adjustment and personalisation of the chemotherapy according tot the individual genotypes combination in each patient.
Association of polymorphisms of the genes involved in cyclophosphamide and doxorubicin metabolism with their toxicity in breast cancer patients
Докторска дисертација одбранета во 2021 година на Медицинскиот факултет во Скопје, под менторство на проф. д–р Михаил Кочубовски.
Keywords: breast cancer, GSTP1 gene polymorphism, cyclophosphamide, doxorubicin, toxic effects